An update on X-Linked agammaglobulinaemia: clinical manifestations and management. Issue 6 (December 2019) - Shillitoe, Benjamin Martin James; Gennery, Andrew R.
Abstract : Purpose of review: X-linked agammaglobulinaemia (XLA) is a congenital defect of development of B lymphocytes leading to agammaglobulinaemia. It was one of the first primary immunodeficiencies described, but treatment has remained relatively unchanged over the last 60 years. This summary aims to outline the current outcomes, treatments and future research areas for XLA. Recent findings: Immunoglobulin therapy lacks IgA and IgM, placing patients at theoretical risk of experiencing recurrent respiratory tract infections and developing bronchiectasis despite best current therapy. Recent cohort studies from Italy and the USA conform that bronchiectasis remains a major burden for this group despite best current efforts. However, gene therapy offers a potential cure for these patients with proven proof of concept murine models. Summary: The potential limitations of current immunoglobulin therapy appear to be confirmed by recent cohort studies, and therefore further work in the development of gene therapy is warranted. Until this is available, clinicians should strive to reduce the diagnostic delay, regularly monitor for lung disease and individualize target immunoglobulin doses to reduce infection rates for their patients.